Usefulness of mobile learning (M-learning) in learning foreign languages - Giedrė Paurienė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
The study aims to discuss mobile learning of foreign languages of the students of the study programme of Preschool Education at Kaunas Higher Education Institution, with a focus on the use of mobile applications. The study objectives are to define the concept of mobile learning and reveal learners’ attitudes toward the use of mobile applications in foreign language learning. The following questions can specify the research problem: How do students perceive the usefulness of mobile applications for foreign language learning? What aspects (e.g., interactivity, content, users’ experience) influence students’ opinions on mobile applications? The question of whether students consider mobile applications beneficial for foreign language learning is significant, as the answer to it reveals the effectiveness of M-Learning and its impact on students’ motivation. Due to time constraints, the study was conducted in only one study programme, so it is not possible to draw specific generalisations for the entire institution regarding the research problem. In this case, the research data can only be used to provide certain trend insights, present findings, and discuss issues. The study should be considered an exploratory research. The conclusions state that mobile learning is a dynamic and interactive form of learning that enables access to educational resources anytime and anywhere. It relies on the use of technologies such as smartphones, laptops, and tablets, which provide opportunities to use various learning applications, games, and materials. Mobile learning promotes individual learning, increases students’ engagement, and offers possibilities to personalise the learning process. Learners consider mobile applications useful for foreign language learning, especially due to their interactivity and the possibility of self-directed learning. Learners’ attitudes towards mobile applications in foreign language learning are shaped by several key aspects. These include interactivity, content, easy and intuitive user’s interface, and the ability to adapt the learning process according to individual needs and progress.